Analisis Penerjemahan Teks Berbahasa Arab dalam Buku Ilmu Balaghah Tarjamah Jauhar Maknun Karya Imam Akhdlori: Analisis Penerjemahan Teks Berbahasa Arab dalam Buku Ilmu Balaghah Tarjamah Jauhar Maknun Karya Imam Akhdlori - Gema Mutakabbir Gema Mutakabbir; Supriadi Rinaldi; Nursyamsiah Nunung (University of Darussalam Gontor, 2023)
Abstract Arabic texts can be understood in their meaning through the process of translation which require specific techniques. Translation techniques will offer resolutions to the translation difficulties encountered by translators. The purpose of this research is to describe the translation techniques from Arabic to Indonesian in the book